Spectrophotometric Determination of Copper(II)with Phenanthrenequinone Monosemicarbazone - Rai, H.C.; Kashyap, Patanjali; Ranjan Kumar, Shiv; Shalamuddin (Asian Journal of Chemistry, 2010)
Investigations on the use of phenanthrenequinone monosemicarbazone as a colorimetric reagent for copper have been made. Optimum conditions for the determination and selectivity of the method have been studied.